Hutang Luar Negeri Pemicu Krisis Ekonomi Indonesia - Anwar Na'im (Unisia, 2001)
The multidimensional crisis in Indonesia today, is a real reflection of the government policy engineering, which fully relies on the foreign debt. This kind of crisis, therefore, can be seen as the implication of the implementation of the wrong, economic policies as occuring in many developing countries.